(untitled) (Research, Society and Development, 2021)
The El Niño and La Niña climate phenomena currently receive more attention due to the fact that their events occur more frequently influencing the regional and global climate. In the methodology analyzed statistical calculations of data in the historical period from 1985 to 2016, identifying the divergent variations from the calculated average thus finding the anomalies of rainfall regimes, correlating with years of records of El Niño and La Niña climate events were identified climate anomalies of great impact in the municipalities of Manaus, Itacoatiara, Eirunepé and São Gabriel da Cachoeira, which is why the citizen and the industry should pay attention to the registration of such events, because the rainfall patterns influence from production of food to power generation, floods or droughts of the rivers of the Amazon.